Towards the self and away from the others: evidence for self-prioritization observed in an approach avoidance task - Roy, Neelabja; Karnick, Harish; Verma, Ark (Frontiers in Psychology, 2023)
Processing advantages arising from self-association have been documented across various stimuli and paradigms. However, the implications of “self-association” for affective and social behavior have been scarcely investigated. The approach-avoidance task (AAT) offers an opportunity to investigate whether the privileged status of the “self” may also translate into differential evaluative attitudes toward the “self” in comparison to “others”. In the current work, we first established shape-label associations using the associative-learning paradigm, and then asked the participants to engage in an approach-avoidance task to test whether attitudinal differences induced on the account of self-association lead to participants having different approach-avoidance tendencies toward the “self-related” stimuli relative to the “other-related” stimuli. We found that our participants responded with faster approach and slower avoidance tendencies for shapes associated with the “self” and slower approach and faster avoidance tendencies for the shapes associated with the “stranger.” These results imply that “self-association” may lead to positive action tendencies toward “self-associated” stimuli, and at the same time lead to neutral or negative attitudes toward stimuli not related to the “self”. Further, as the participants responded to self-associated vs. other-associated stimuli cohorts, these results may also have implications for the modulation of social group-behaviors in favor of those like the self and against those in contrast to the self-group.